Occupational choice of return migrants in Moldova - Daniela Borodak; Matloob Piracha (Institute for the Study of Labor (IZA), 2010)
This paper analyses the occupational choice of return migrants. Using the CBSAXA data on different aspects of migration in Moldova, we find that those who stayed illegally in the host country tend to go in wage employment on return to the home country. We also show that relatively better educated tend not be in formal employment, i.e., appear not to participate in the labour market whereas those with relatively lower skills or who obtained worse than expected outcome in the host country are more likely to be wage employed in the home country on return. We discuss intuition of these paradoxical results in the paper.
Keywords: C35; F22; J24; 330; occupational choice; return migration; sample selection; Moldova; Rückwanderung; Berufswahl; Qualifikation; Moldawien